The challenges and strategies in sustaining business growth among young muslim entrepreneurs in Kedah - Aufa Rahwani, Lukman (2025)
Islamic entrepreneurship emphasizes honesty, fairness, transparency, and social responsibility, framing business as both a path to financial success and an act of worship. Nowadays, young entrepreneurs face numerous challenges, including limited access to Shariah-compliant financing, stringent collateral and procedural requirements, a lack of experience and mentorship, difficulties in talent recruitment, resource management issues, and regulatory complexities. Hence, this study was conducted to examine the challenges faced by young Muslim entrepreneurs in sustaining business growth while adhering to Islamic ethical principles. The study data collection used a qualitative approach through semi-structured interviews with entrepreneurs from the Kedah region. There are 5 Muslim entrepreneurs involved in this study. The findings of this study reveal that, despite facing intense market competition and the challenge of balancing business demands with religious obligations, young Muslim entrepreneurs undertake proactive measures such as diligently monitoring costs, soliciting customer feedback, and implementing stringent quality control to ensure smooth business operations and sustainable growth. This research contributes to understanding the intersection of faith and entrepreneurship and offers actionable recommendations for policymakers, educators, and financial institutions to enhance access to Islamic financing, strengthen entrepreneurial education, and develop supportive ecosystems. By aligning business sustainability with Islamic values, young Muslim entrepreneurs can build resilient enterprises that promote both economic and social welfare